PENGARUH MOBILITAS SOSIAL TERHADAP PERUBAHAN BAHASA - Latif, Saiful (EDUKASI, 2016)
Language is a sound system that used people in a communication to share idea and feeling in a society. There are three terms that have to know by a language learner. They are langage, Langue, dan parole. In linguistics study, the object of linguistics is parole. In the process of communication, usually make a linguistic change and linguistic shift. Although, linguistic change and linguistic shift are made by a language user, but also he or she maintain his or her language. A couse of linguistic change and linguistic shift is social mobility. Social mobility is a process of moving from a social class to another social class. Social class can be devided become two kinds. They are vertical social class and horizontal social class.     Key words: Language change, social mobility